General Burden of Adult Atopic Dermatitis: An Observational Study of Disease Perceptions among Patients and Dermatologists in France - Angèle Soria; Claire Thénié; Christina Bienenfeld; Delphine Staumont-Sallé (Medical Journals Sweden, 2021)
It is important to understand patients' and dermatologists' perceptions of various aspects of atopic dermatitis, but there is a lack of studies on quality of life and stakeholder viewpoints in this therapy area. The aim of this study was to compare patients' and dermatologists' viewpoints regarding the impact of atopic dermatitis that is uncontrolled by topical corticosteroids. Data were collected from 348 adult patients who responded to self-administered questionnaires, and 150 telephone interviews with the dermatologists who selected them. Patients and dermatologists reported both convergent and divergent assessments of the impact of atopic dermatitis and its treatment. Notable areas of agreement were regarding the safety of emollients, the time required and difficulty of applying topical corticosteroids, especially to certain parts of the body. Divergent views involved the perceived efficacy of available treatments and the impact of atopic dermatitis on professional life. A greater understanding of these differences would help dermatologists to optimize patient care.